Pelatihan Kerja Memoderasi Pengaruh Tingkat Pendidikan dan Pengalaman Kerja Pada Efektivitas Pengendalian Internal - Mahendra, Made Andiva; Ramantha, I Wayan (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 1 (2018), 2018)
The purpose of this study is to prove empirically about the effevt of educational level and work experience on the effectiveness of internal control with job training as a moderating variable. This research conducted at Kantor Inspeksi Denpasar, PT Bank Rakyat Indonesia (Persero) Tbk. The number of samples in this study were 51 respondents, with sampling using purposive sampling method. The data collected by questionnaires and data analysis techniques using moderated regression analysis (MRA). The results of this study proves empirically that educational level has not effect on the effectiveness of internal control, work experience has a positive effect on the effectiveness of internal control, job training stengthens the influence of educational level on the effectiveness of internal control, and job training is unable to moderate the effect of work experience on the effectiveness of internal control. Keywords : JobTraining, educational level, work experience, effectiveness of internal control.